2016
DOI: 10.1021/acsami.6b03424
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Stable Transparent Superhydrophobic Polydimethylsiloxane Films by Duplicating via a Femtosecond Laser-Ablated Template

Abstract: Realizing superhydrophobicity, high transparency on polydimethylsiloxane (PDMS) surface enlarges its application fields. We applied a femtosecond laser to fabricate well-designed structures combining microgrooves with microholes array on mirror finished stainless steel to form a template. Then liquid PDMS was charged for the duplicating process to introduce a particular structure composed of a microwalls array with a certain distance between each other and a microprotrusion positioned at the center of a plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 27 publications
0
73
0
Order By: Relevance
“…Gong et al [38] recently reported a convenient and efficient duplicating method, being capable to form a transparent PDMS surface with superhydrophobicity in mass production. They claimed that the fabrication process had extensive application potentials.…”
Section: Transparent Non-wettable Coatings From Pattern Transfer To Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Gong et al [38] recently reported a convenient and efficient duplicating method, being capable to form a transparent PDMS surface with superhydrophobicity in mass production. They claimed that the fabrication process had extensive application potentials.…”
Section: Transparent Non-wettable Coatings From Pattern Transfer To Pmentioning
confidence: 99%
“…The superhydrophobic PDMS surfaces were also tested for thermal stability up to 325 • C. . The SCA of this optimal surface is 154.5° ± 1.7° and SA 6° ± 0.5°; (d) Sample of optimally designed PDMS coated on the paper; and (e) it was held up to keep a certain distance (10 cm) from the paper; (f) Transparency of the optimal designed surface is over 91% in the visible light wavelength [38].…”
Section: Transparent Non-wettable Coatings From Pattern Transfer To Pmentioning
confidence: 99%
“…Recently, Gong et al [102] demonstrated an efficient method to produce a flexible superhydrophobic PDMS surface with high transparency. Using femtosecond laser processing, they fabricated a stainless steel template, which was comprised of an array of microgrooves with microholes, as shown in Figure 9a.…”
Section: Reactive Ion Etchingmentioning
confidence: 99%
“…Synthesis of stable metallic Cu NPs is a challenge as they are easy to be oxidized rapidly in air or aqueous media. Dopamine is an important catecholamine neurotransmitter and plays an important role in central nervous systems . Because of catechol and amine functional groups, dopamine can mimic the strong adhesive foot protein Mytilus edulis foot protein 5 (Mefp‐5) .…”
Section: Introductionmentioning
confidence: 99%